2020
DOI: 10.1186/s13052-020-00890-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal factors associated with low birth weight in public hospitals of Mekelle city, Ethiopia: a case-control study

Abstract: Background Mothers in low socio-economic conditions frequently have low birth weight infants. Inaddition Physically demanding work during pregnancy also contributes to poor fetal growth. During gestation a woman needs balanced nutrition for a healthy outcome. Women with inadequate nutritional status at conception are at greater risk of aquiring disease; their health usually depends on the availability and consumption of balanced diet, and therefore they are unlikely to be able to resist with their high nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
5
22
0
Order By: Relevance
“…As the feature importance rank identified, Gender of the child, marriage to birth interval, mother’s occupation and mother's age were the top four critical predictors of low birth weight in Ethiopia, according to the XGB model. This study is roughly in line with the findings research [ 6 , 10 , 14 , 16 , 22 ]. The findings of this study are similar to those of the subsequent analyses.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As the feature importance rank identified, Gender of the child, marriage to birth interval, mother’s occupation and mother's age were the top four critical predictors of low birth weight in Ethiopia, according to the XGB model. This study is roughly in line with the findings research [ 6 , 10 , 14 , 16 , 22 ]. The findings of this study are similar to those of the subsequent analyses.…”
Section: Resultssupporting
confidence: 94%
“…Several studies in Ethiopia have been conducted to assess the prevalence and risk factors for low birth weight and have found that low birth weight ranges from 6 to 29.1%. Furthermore, low birth weight was associated with the infant’s sex, pregnancy-induced hypertension, ANC follow-up, preterm, parity, and residence [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, studies conducted in Hosanna town, Gondar, Mekelle, and a systematic review and meta-analysis in Ethiopia showed similar findings. 10,23,25,27 These might be because having a birth at an early age had a higher risk of delivering a baby with LBW. 28 Pregnant teens are more likely to develop pregnancy-related high blood pressure and anemia, which will lead to preterm labor and delivery.…”
mentioning
confidence: 99%
“…This result is comparable with studies conducted in Bale zone hospitals, the University of Gondar, Hosanna town, and Mekelle. 5,10,13,27 There will be a chance for monitoring of fetal wellbeing and timely intervention of feto-maternal problems when there is an ANC visit. Additionally, there will be routine nutritional and medical advice, as well as the provision of supplementations during ANC visits.…”
mentioning
confidence: 99%
“…VSD was the most commonly reported in 53.2% patients followed by coarctation of aorta (17%) [3], suggesting the screening of low birth weight neonates for congenital cardiac defects. Godfrey [21]. Further studies may be conducted to identify risk factors and manage accordingly.…”
Section: Discussionmentioning
confidence: 99%